THE WAR AGAINST IMPUNITY FOR INTERNATIONAL CRIME: OPTICAL ILLUSION? - Ovide Egide Manzanga Kpanya (Universitas Lampung, 2021)
Deliberation on the imprescriptibility principle in international criminal law motivates determination towards the principle's function against impunity for international crimes. It is indeed a question of confronting this principle with judicial responsiveness, which relies on the speed of the criminal response. However, the current criminal response seems somewhat poorly considering the arising crimes. The poor execution enables criminals than the victims, which injures society. Therefore, it leads to inadmissibility. It is for this purpose that imprescriptibility arises and imposes itself comfortably. The research's conclusion attempts to demonstrate another facet of imprescriptibility. Imprescriptibility includes the impunity's ineffectiveness which passes irreversibly where ipso facto ensures impunity. This condition was perceived as a temporary and partial absence of justice that produced its socio-legal effects. Thus, the uncertainty of a judicial reaction resulting implicitly from this principle foster indolence in society. Over time, this would unsurprisingly lead to a denial of justice and eternal impunity.